Freedom of expression in Egypt: how long hair, pink shirts, novels, amateur videos and facebook threaten public order and morality!. (September 2016) - Mansour, Khaled
Abstract: Freedom of expression suffers from a ferocious crackdown in Egypt because of gaping narcissistic injuries to a chauvinist, patriarchal national psyche that has been repackaged in Egypt's early post‐colonial years. Decades of cultural and socio‐economic decay has torn Egypt's stereotypical psyche between claims of grandeur and righteousness on the one hand and a reality of failures and debasement on the other hand. Dislocated, many Egyptians are desperate and willing to submit to any comforting system of meaning. Their alienation and sense of shame drive them to seek a clean origin and to disavow reality, a state that is conducive to an obsession with blaming the other, or the minority or the neighboring communities, for instigating this shame. There is a symbiotic deadlock of the impossible return to an imagined past and the feared submission to an ill‐defined new. This creates a state of neurosis where the two essentialist "selves" propagated by the religious and neoliberal elites are meant to preserve a status quo under the benevolent hand of the father/dictator. A challenge to this setup means also a challenge to the father whose protection is sought and loathed in such a torturous neurotic state whose end or dissolution could mean to many the end of the world as they know it. For Egypt to get out of this quagmire, deep political and institutional reforms will have to evolve through social resistance and transformation. This will take time because ultra‐nationalism and patriarchy are instrumentalized and integral to deep vested material and psychological interests.